Sartre’s ‘Freedom’ and Society: Existentialist’s Dilemma in Naturalistic View - Ghosh, Anirban; Chakrabarti, Malabika (Philosophy and Realistic Reflection, 2025)
Existentialism dealt with the essence of human existence and established its priority over others where freedom of act for a conscious mind was the prime factor. Jean-Paul Sartre emphasized on such individual freedom with imposition of some liabilities over it for humanity. Sartre and other philosophers furnished different causes for such restrictions. However, the general concept of natural and evolutionary science is also competent and capable to explain this reservation of freedom. Present article will discuss the background of why such an interruption was required in Sartre’s concept of complete freedom. At the same time the article will analyse whether and how far Sartre’s concept of complete freedom of a conscious mind was relevant from the historical, social and evolutionary biological perspective with an analysis of consciousness from scientific perspective. Examining Sartre’s dilemma on freedom and its relevance with a naturalistic angle, authors tried to answer whether negotiation for freedom was a humanitarian attribute or an obvious natural compulsion for the sustainability of the naturally evolving human association and community. Finally, importance of Sartre in the context of the socio-political scenario of that time has been clarified to justify his views. Simultaneously, the act of a conscious mind in a natural community of human association has been explained to show why it is actually compelling to make a trade-off for freedom in a society.